Possible Future Directions for Oceanographic Research in India - Sudhakar M.; Ramesh R. (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
Most oceanographic research to date pertains to the surface ocean which is well lit by the Sun or to benthic organisms that have been seen by dredging and coring the sea floor. We are just beginning to know about the organisms in the deep ocean after the developments of remotely operated vehicles and underwater instruments.